Electrokinetic study of calcium carbonate and magnesium hydroxide particles in lime softening. (1st November 2020) - Zhang, Lu; Mishra, Dinesh; Zhang, Kailun; Perdicakis, Basil; Pernitsky, David; Lu, Qingye
Highlights: pH/temperature/aging/inorganic carbon impacts zeta potential (ZP) of Mg(OH)2 . pH/temperature/aging/inorganic carbon/divalent cations impacts ZP of CaCO3 . Mg(OH)2 can change ZP of CaCO3 from negative chargely to positively charged. Silica/clay/humic acid shifts the ZP of Mg(OH)2 from positive to negative. Silica/clay/humic acid shifts the ZP of CaCO3 to more negative. Abstract: Significant effort has been made to measure and understand the surface charge of CaCO3 and Mg(OH)2 particles. Many laboratory experiments have been reported on zeta potential of natural and prepared CaCO3 and a few have also been published for Mg(OH)2, however, there are very few reported measurements of zeta potential of CaCO3 and Mg(OH)2 particles at conditions relevant to lime softening, despite lime softening being a common and established process for water treatment. The present study aims to understand the interactions and electrokinetic properties of these two particles in lime softening. Effects of various experimental parameters such as pH, temperature, aging, inorganic carbon (CO3 2− /HCO3 − ), and divalent cations (Ca 2+ /Mg 2+ ) on the electrokinetic properties (i.e. zeta potential) of CaCO3 and Mg(OH)2 particles were individually studied. The interactions between humic acid (mimicking natural organic matter), silicate (representing silica), clay (mimicking suspended solids) and CaCO3 /Mg(OH)2 particles were studied, as well as the interactions between CaCO3 and Mg(OH)2 . Thermodynamic modeling was used to predict precipitates as a function of solution chemistry and assist with data interpretation. The results provide considerable insight into factors that are of importance to lime softening. Graphical abstract: Image, graphical abstract